Flexible operation and integration of high-temperature heat pumps using large temperature glides - Knorr, Lukas; Schlosser, Florian; Horstmann, Nils; Divkovic, Denis; Meschede, Henning (Applied Energy)

Break-even of high-temperature heat pump integration for milk spray drying - Schlosser, Florian; Zysk, Sebastian; Walmsley, Timothy G.; Kong, Lana; Zühlsdorf, Benjamin; Meschede, Henning (Energy Conversion and Management)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

On the potential of temporally resolved GHG emission factors for load shifting: A case study on electrified steam generation - Wolf, Isabel; Holzapfel, Peter K.R.; Meschede, Henning; Finkbeiner, Matthias (Applied Energy)
Keywords: Management; Monitoring; Policy and Law; Mechanical Engineering; General Energy; Building and Construction

Design approach to extend and decarbonise existing district heating systems - case study for German cities - Divkovic, Denis; Knorr, Lukas; Meschede, Henning (International Journal of Sustainable Energy Planning and Management)
This paper aims to present an approach for the planning of carbon low heat supply in a future district heating system based on open data for German cities with existing district heating networks. One focus is on the integration of industrial waste heat and the uncertainty of future waste heat sources as well as restrictions on the use of biomass. For that purpose, knowledge about the energy demand is necessary. In a first step it is shown how the demand around a heating network is estimated with spatial data and a load profile is generated. Local available heat sources are examined according to their suitability and their kind of integration in the heating network. As heat production from different units are optimised, the development of a simulation model will be presented. The simulation is based on the optimisation of the operational costs of the used technologies for heating supply. Different scenarios covering various technologies and economic assumptions are applied. The results show the levelized costs of heating as well as the ecological performance. A sensitivity analysis shows the importance of uncertainties for the economic assumptions. The results showing levelized costs of heating as well as the ecological performance underlining the advantage of excess heat integration.
Keywords: Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Assessment of Energy Efficiency and Flexibility Measures in Electrified Process Heat Generation Based on Simulations in the Animal Feed Industry - Knorr, Lukas; Schlosser, Florian; Meschede, Henning (Journal of Sustainable Development of Energy, Water and Environment Systems)
Keywords: Energy Engineering and Power Technology; Water Science and Technology; Environmental Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Hybrid renewable energy utility systems for industrial sites: A review - Walmsley, Timothy Gordon; Philipp, Matthias; Picón-Núñez, Martín; Meschede, Henning; Taylor, Matthew Thomas; Schlosser, Florian; Atkins, Martin John (Renewable and Sustainable Energy Reviews)
Keywords: Renewable Energy; Sustainability and the Environment

Carbon insetting as a measure to raise supply chain energy efficiency potentials: Opportunities and challenges - Ebersold, Felix; Hechelmann, Ron-Hendrik; Holzapfel, Peter; Meschede, Henning (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Regenerative Energien für einen effizienten Betrieb von Presshärtelinien - Knorr, Lukas; Jungeilges, André; Pfeifer, Florian; Burmeister, Sascha Christian; Meschede, Henning

Economic Integration of a High-Temperature Heat Pump with Flexible Part-load Operation - Knorr, Lukas; Schlosser, Florian; Meschede, Henning

A review of 100% renewable energy scenarios on islands - Meschede, Henning; Bertheau, Paul; Khalili, Siavash; Breyer, Christian (WIREs Energy and Environment)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Chapter III – Using Energy More Efficiently. Preparing the Ground with Energy Efficiency. - Hechelmann, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Schlüter, Alexander (Sustainable and Smart Energy Systems for Europe's Cities and Rural Areas)

Chapter III – Using Energy More Efficiently. Saving Energy in Industry and Commerce. - Schlosser, Florian; Hechelmann, Ron-Hendrik; Meschede, Henning; Schlüter, Alexander (Sustainable and Smart Energy Systems for Europe's Cities and Rural Areas)

Insetting in the Context of Industrial Climate Protection Strategies - Ebersold, Felix; Hechelmann, Ron-Hendrik; Holzapfel, Peter; Meschede, Henning

Techno-economic Potential of High-Temperature Heat Pump Integration - Schlosser, Florian; Walmsley, Timothy; Kong, Lana; Zühlsdorf, Benjamin; Meschede, Henning

Development of an Advanced Digitalised Approach to Reduce Greenhouse Gas Emissions in the Industrial Sector - Naumann, Marius; Schlosser, Florian; Meschede, Henning

Sector Coupling and Storage are Crucial for Green Energy - Meschede, Henning; Khripko, Diana; Meschede, Eva (Sustainable and Smart Energy Systems for Europe's Cities and Rural Areas)

Making Energy Demand More Flexible - Khripko, Diana; Meschede, Henning; Meschede, Eva (Sustainable and Smart Energy Systems for Europe's Cities and Rural Areas)

Investigation on future district heating systems for German cities with existing district heating network - Divkovic, Denis; Knorr, Lukas; Meschede, Henning

Energy Efficiency as Key for Climate Neutral Business - Knorr, Lukas; Meschede, Henning

Assessment of Energy Efficiency and Flexibility Measures in Electrified Process Heat Generation Based on Simulations in the Animal Feed Industry - Knorr, Lukas; Schlosser, Florian; Meschede, Henning

Energy-efficient industrial processes as part of an integrated sustainable energy system - Meschede, Henning

Energy Efficiency and Energy Supply in Industrial Parks - Meschede, Henning

Energy Efficiency as Key for Climate Neutral Business - Meschede, Henning

Smart Energy Systems on Off-grid Islands - Meschede, Henning

Energy Efficiency in Industrial Processes - Meschede, Henning

Energy Efficiency Technologies in Germany - Meschede, Henning

Energie einsparen in Industrie und Gewerbe - Schlosser, Florian; Hechelmann, Ron-Hendrik; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Mit Energieeffizienz Grundlagen legen - Hechelmann, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Wer grüne Energie will, muss auch koppeln und speichern - Meschede, Henning; Khripko, Diana; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Energienachfrage flexibler gestalten - Khripko, Diana; Meschede, Henning; Meschede, Eva (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Wer grüne Energie will, muss auch koppeln und speichern - Meschede, Henning; Khripko, Diana; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities and Smart Rural Areas)

Energie einsparen in Industrie und Gewerbe - Schlosser, Florian; Hechelmann, Ron-Hendrik; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Mit Energieeffizienz Grundlagen legen - Hechelmann, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Analysis on the demand response potential in hotels with varying probabilistic influencing time-series for the Canary Islands - Meschede, Henning (Renewable Energy)

Keine Klimaneutralität ohne Energieeffizienz – Wie Datenbanken helfen können, Energieeffizienzpotenziale zu heben - Ebersold, Felix; Reineke, Patrick; Meschede, Henning; Hesselbach, Jens (BWK Das Energie Fachmagazin)

Energy efficiency in industrial processes – best practice - Meschede, Henning

Assessment of Flexibilisation Potential by Changing Energy Sources Using Monte Carlo Simulation - Dunkelberg, Heiko; Sondermann, Maximilian; Meschede, Henning; Hesselbach, Jens (Energies)
In the fight against anthropogenic climate change, the benefit of the integration of fluctuating renewable energies (wind and photovoltaics) into the electricity grid is a widely proved concept. At the same time, a fluctuating and decentralised supply of energy, especially at lower voltage levels, leads to a local discrepancy in the power balance between generation and consumption. A possible solution in connection with demand side management is the grid-oriented flexibilisation of energy demand. The present study shows how the use of an innovative hybrid-redundant high-temperature heat system (combined heat and power (CHP), power-to-heat system (PtH), gas boiler) can contribute to a flexibilisation of the electrical energy demand of plastics processing companies. In this context, the flexibilisation potential of a company is to be understood as the grid-related change of the energy supply through a change of the energy sources within the framework of the process heat supply. For this purpose, an omniscient control algorithm is developed that specifies the schedule of the individual system components. A sensitivity analysis is used to test the functionality of the control algorithm. Determination of the electrical flexibilisation potential is carried out via a comprehensive simulation study using Monte Carlo methods. For this purpose, the residual load curves of four characteristic distribution grids with a high share of renewable energies as well as heat load profiles of injection moulding machines are taken into consideration. A frequency distribution provides information on the electrical flexibilisation potential to be expected depending on the various combinations. The evaluation is carried out using a specially introduced logic, which identifies grid-relevant changes in the company's power consumption as flexibilisation potential based on a reference load curve. The results show that a reliable energy supply for production is possible despite flexibilisation. Depending on the grid under consideration, there are differences in the exploitation of the potential, which essentially depends on the installed renewable capacity. Depending on the scenario under consideration, an average of up to 1486 kWhel can be shifted in a positive direction and 1199 kWhel in a negative direction.

On the impact of probabilistic weather data on the economically optimal design of renewable energy systems – a case study on La Gomera island - Meschede, Henning; Hesselbach, Jens; Child, Michael; Breyer, Christian (International Journal of Sustainable Energy Planning and Management)
Renewable energy and storage systems are widely discussed to minimise the impact of global warming. In addition to the temporal resolution of simulation tools, also the chosen input data might have a strong impact on the performance of renewable energy systems, and energy storage systems in particular. This study analyses the impact of probabilistic weather data on the design of renewable energy systems. The main objective is hereby the determination of the robustness of a recently state-of-the-art design process of a 100% renewable energy and storage system with varying probabilistic input data. The island of La Gomera, Canary Islands, is taken as a case study. Although all analysed systems show some variance in their results, the combination of vehicle-to-grid and power-to-hydrogen shows the best economic performance. Hereby, small island energy systems depending heavily on wind energy show higher variations than those with high shares of solar energy. This analysis illustrates clearly that the choice of one historical reference year is not suitable to determine the expected performance of an energy system. To learn about their sensitivity, synthetic probabilistic inputs as applied in this study are a good way to determine both the expected mean values and their variance.

Classification and clustering of the German plastic industry with a special focus on the implementation of low and high temperature waste heat - Dunkelberg, Heiko; Schlosser, Florian; Veitengruber, Frank; Meschede, Henning; Heidrich, Tobias (Journal of Cleaner Production)

On the transferability of smart energy systems on off-grid islands using cluster analysis – A case study for the Philippine archipelago - Meschede, Henning; Esparcia, Eugene A.; Holzapfel, Peter; Bertheau, Paul; Ang, Rosario C.; Blanco, Ariel C.; Ocon, Joey D. (Applied Energy)

Automatic Time Series Segmentation as the Basis for Unsupervised, Non-Intrusive Load Monitoring of Machine Tools - Seevers, J-P.; Johst, J.; Weiß, T.; Meschede, Henning; Hesselbach, J. (Procedia CIRP)

Increased utilisation of renewable energies through demand response in the water supply sector – A case study - Meschede, Henning (Energy)

Evaluation of a Stratified Tank based Heat Recovery Loop via Dynamic Simulation - Schlosser, Florian; Hechelmann, Ron-Hendrik; Meschede, Henning; Matthias, Philipp; Walmsley, Timothy G. (Chemical Engineering Transactions)

Assessment of probabilistic distributed factors influencing renewable energy supply for hotels using Monte-Carlo methods - Meschede, Henning; Dunkelberg, Heiko; Stöhr, Fabian; Peesel, Ron-Hendrik; Hesselbach, Jens (Energy)

Classification of global island regarding the opportunity of using RES - Meschede, Henning; Holzapfel, Peter; Kadelbach, Florian; Hesselbach, Jens (Applied Energy)